Determination Of Factors Affecting The Ethical Behavior Of Internal Auditors In Higher Education - Arifudin Arifudin; Satia Nur Maharani; Eka Ananta Sidharta (International Journal of Business and Quality Research, 2023)
The focus of this research is to find out how the auditor's perception is related to determining the factors that influence the ethical behavior of auditors in the college environment. This research was conducted at the Internal Supervisory Unit of a state university. This study uses a phenomenological approach as part of qualitative research, data collection using interviews with auditors in the financial section of the Internal Supervisory Unit of State Universities. Based on research on the factors that influence the ethical behavior of auditors in the tertiary environment, there is an auditor's ethical reasoning, the professional commitment of an auditor, environmental conditions related to the influence of superiors, and also ethical, moral support, as well as the spirituality of the auditor